Organoleptic Evaluation and Consumer Preferences for Singkil Tea and Kombucha Products (Premna corymbose Rottl. Et Willd) - Teguh Pribadi; Zulfa Zakiyyah; Nurul Anisa; Imam Wijayadi; Masitah Masitah; Eadvin Rosrinda Awang Sari; Ingghrid Ranesti Clarita Hadi; Ayu Indah Rahmawati (Universitas Labuhanbatu, 2025)
Background: Changes in tea consumption trends present opportunities for the tea industry, especially as alternative raw materials have been tested in recent years to develop tea and kombucha with distinct organoleptic and functional properties. This study evaluates the organoleptic characteristics and consumer preferences for Singkil tea and Singkil kombucha. Methodology: A sensory evaluation was conducted with 30 untrained panelists to assess color, aroma, taste, texture, and overall acceptability using a hedonic scale. Additionally, the alcohol content was measured. Findings: The results of the hedonic test indicated that all treatments fell into category 3